Bortezomib-induced painful neuropathy in patients with multiple myeloma - Bilińska, Małgorzata; Usnarska-Zubkiewicz, Lidia; Pokryszko-Dragan, Anna (Contemporary Oncology/Współczesna Onkologia, 2013)
Neurotoxicity towards the peripheral nervous system which appears clinically in the form of painful neuropathy is an essential dose-limiting factor during the treatment of multiple myeloma. In this review article different forms of this painful neuropathy are presented together with currently available diagnostic tools which are usually applied to confirm the diagnosis. Also, the most often used neurological scales estimating neurological deficit are presented. Special attention is paid to the management of the reversibility of bortezomib-induced neuropathic pain.